2014
DOI: 10.1111/pbi.12220
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of microRNAs and other small RNAs in barley between water and drought conditions

Abstract: Drought is a major constraint to crop production, and microRNAs (miRNAs) play an important role in plant drought tolerance. Analysis of miRNAs and other classes of small RNAs (sRNAs) in barley grown under water and drought conditions reveals that drought selectively regulates expression of miRNAs and other classes of sRNAs. Low-expressed miRNAs and all repeat-associated siRNAs (rasiRNAs) tended towards down-regulation, while tRNA-derived sRNAs (tsRNAs) had the tendency to be up-regulated, under drought. Antise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
124
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(133 citation statements)
references
References 56 publications
7
124
0
2
Order By: Relevance
“…The abundance of small RNA reads in the control libraries of the two species was comparable to those reported in Lagenaria siceraria, Cucurbita moschata, Cucurbita pepo and watermelon (Jagadeeswaran et al 2012). However, control and drought stress libraries of Medicago truncatula and Hordeum vulgare were reported to show the highest peak of small RNA reads at 24-nt and second highest reads for 21-nt size class Hackenberg et al 2015). Similar kind of size distribution of drought stressed small RNA libraries of the two species in this study have been observed with the highest peak of total small RNA reads at 24-nt followed by 21-nt size class (Figs.…”
Section: Resultssupporting
confidence: 75%
“…The abundance of small RNA reads in the control libraries of the two species was comparable to those reported in Lagenaria siceraria, Cucurbita moschata, Cucurbita pepo and watermelon (Jagadeeswaran et al 2012). However, control and drought stress libraries of Medicago truncatula and Hordeum vulgare were reported to show the highest peak of small RNA reads at 24-nt and second highest reads for 21-nt size class Hackenberg et al 2015). Similar kind of size distribution of drought stressed small RNA libraries of the two species in this study have been observed with the highest peak of total small RNA reads at 24-nt followed by 21-nt size class (Figs.…”
Section: Resultssupporting
confidence: 75%
“…In general, low-count miRNAs are considered to have weak or low biological importance or mRNA degradation effect [51], because these low-count miRNAs have a quick turnover in evolution [52]. In our study sRNA turnover or degradation may better explain why few and low abundance transgene-derived reads were obtained in the libraries of the transformed peanut lines.…”
Section: Discussionmentioning
confidence: 84%
“…During the last few years, an emerging number of drought-related miRNAs have been reported in several crop plants, such as barley (Hordeum vulgare; Hackenberg et al, 2015), rice (Oryza sativa; Zhou et al, 2010;BarreraFigueroa et al, 2012), cotton (Xie et al, 2015), potato (Solanum tuberosum; Zhang et al, 2014), maize (Zea mays; Li et al, 2013b), tomato (Candar-Cakir et al, 2016), cowpea (Vigna unguiculata; Barrera-Figueroa et al, 2011), peach (Prunus persica; Eldem et al, 2012), and poplar Ren et al, 2012). Recently, Sun et al (2015) described changes in grape miRNA abundance induced by cold stress and Pantaleo et al (2016) characterized novel miRNAs in virus-infected grapevine contemporaneously subjected to water stress.…”
Section: Conserved and Novel Grapevine Mirnas Respond To Ds In The Twmentioning
confidence: 99%